Desenvolvimento econômico e mercado de trabalho urbano no nordeste brasileiro - Lira, Fernando José de (1994)
The Nortbeast of Braszil presents a recent history that is characterized by two phases: the isolation and the articulation. Intense transfonnations in the region economy at the second phase were stimulated by the dynamism that carne up in the beginning of the 60·s. These transfonnations led to an increase of the regional product, alterations in the productive structure through the adoption of a new work process that caused a reduction of the job offers and on the other hand by its expansion. It W8S also noted that expressive changes happened in the industrialized products wbich reduced the participation of non-durable consumer goods production and the inerease, in a very important way, of the participation of intennediate goods industries directed to a domestic and foreign trade. Therefore, it contributed to inerease the dependence of the Nortbeast in relationto wealthier regions. Thechanges initiated in the industrial setor spread through primary, secondary and tertiary sectors, In the agricultura1 seetor, the transfonnations tumed worker's survival more difficult, increased the capitalist relations, that were manifested in the higher proletarization of rural hand labor, encouraged emigration to the cities, increasing in a large number the participation of the population that worked exclusive1y in urban activities. In the tertiary sector, the changes stimulated the development of tmderemployment, a great di.fferentiation in the productivity Ievels and income, creating a situation that worsen.s the differences existing in the productive structure and in the labor marlcet. UI lV Besides that, there was an excessrve urbenization, increase of income concentration, development of infonna.l activity degree, increase of the nmnbe.rs of illegal workers and more participation of under age people and adults in the labor market. AlI of this, happened associated with the dynamism of the productive aetiviíies, that had never happened in the recent history of the less developed regions in the coutry, The data analysis also showed that the unemployment leveI for both men and women is relative1y low. This occurs beeause in the economical expansion or in the economical retraction, the oscillations in the occupation level are followed by modifications in the participation rate of those that are in the age of work at the labor market. Therefore, the recent infurmality. formality and submersion of the hand labor in the Northeast are assoeiated with an economical increase context, resulting consequent1y in an accumulation of capital, that even carrying out with high rates of expansion, do not repercute in a positive way in the labor market, in the tenns required by the hand labor offering. Thus, the appearance of relative exeeeding population is a result of the standard accwnulation of the regional economy capital, wbich is assoeiated with the way the Northeast was inserted in the national economical contexto So, it is the standard industrialization the main responsible for lhe local economy unsuceessful in absorving in a productive way the urban labor-market population.